Organizational Ethics and Employee Satisfaction: A Cultural Perspective - Swid, Amr (Journal of Leadership, Accountability and Ethics, 2023)
This research examines the relationship between Top management support for ethical behavior, ethical climate, moral awareness, and employee job satisfaction. A total of 200 employees in eight organizations were surveyed using a quantitative method. The results indicated a significant relationship between job satisfaction and top management support for ethical behavior. There is a significant relationship between job satisfaction and the association between ethical behavior and career success. Ethical climate partially mediates the relationship between top management support for ethical behavior and job satisfaction, while moral awareness moderates the relation between ethical climate and job satisfaction. The research discussed implications and recommended future research.